Museum sample and materials and methods from The genetic basis and enigmatic origin of melanic polymorphism in pomarine skuas ( Stercorarius pomarinus ). - Kirstin Janssen; Nicholas I. Mundy (2017)
A key outstanding issue in adaptive evolution is the relationship between the genetics of intraspecific polymorphism and interspecific evolution. Here we show that the pale/dark ventral plumage polymorphism that occurs in both the pomarine skua ( Stercorarius pomarinus ) and Arctic skua ( S. parasiticus ) is the result of convergent evolution at the same locus ( MC1R ), involving some of the same amino acid sites. The dark melanic MC1R allele in the pomarine skua is strongly divergent from the pale MC1R alleles. Whereas the dark allele is closely related to MC1R alleles in three species of great skua ( S. skua , S. maccormicki , S. lonnbergi ), the pale pomarine skua MC1R alleles present a star-like pattern in an intermediate position on the haplotype network, closer to alleles of the long-tailed skua ( S. longicaudus ). Variation at other nuclear loci confirms a close relationship between the pomarine skua and the great skuas. The plumage polymorphism in pomarine skuas might have arisen in the common ancestor of pomarine and great skuas, only being retained in pomarine skuas. Alternatively, the pale and melanic MC1R alleles may have evolved independently in different lineages and been brought together in pomarine skuas by hybridization. In this case introgression of a pale MC1R allele into the pomarine skua from another skua lineage is most likely. Our current data do not permit us to distinguish between these hypotheses, and assaying genome-wide variation holds much promise in this regard. Nevertheless, we have uncovered an intriguing example of a functionally important allele within one species that is shared across species.